Kajian Korosi Struktur Conveyor B Pada Tambang Batubara PT XYZ Di Kabupaten Merangin Provinsi Jambi. - Rizky Yulmansyah (Jurnal Riset Teknik Pertambangan, 2021)
Abstract. Conveyor is one of the tools that is used to move excavated materials such as coal. Conveyor structure is made of carbon steel. However, the conveyor structure can experience a decrease in quality due to corrosion that occurs due to direct contact with coal impurities and its environment. This research was conducted on a conveyor structure consisting of 2 segments with 16 test points along 60 meters. This study aims to determine the type of corrosion, corrosion control conditions applied coating. Methodology in this research is measuring the thickness reduction of the conveyor structure. In this study, observations of environmental conditions include an average air temperature of 280C, an average rainfall of 233 mm and, relative humidity of 87%. The actual thickness measurement of the conveyor structure is using the Ultrasonic Thickness Gauge TT 130. Type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method applied to the conveyor structure is the coating method. The applied coatings are primer coating using Seaguard 5000, intermediate coating using Sherglass FF and, top coating using Aliphatic Acrylic Modified Polyurethane. Abstrak. Conveyor merupakan salah satu alat yang digunakan untuk memindahkan material bahan galian seperti batubara. Struktur conveyor yang digunakan berbahan dasar baja karbon. Namun demikian struktur conveyor dapat mengalami penurunan kualitas yang diakibatkan oleh korosi yang terjadi karena kontak langsung dengan pengotor batubara dan lingkungannya. Penelitian ini dilakukan pada struktur conveyor yang terdiri dari 2 segmen dengan 16 test point sepanjang 60 meter. Penelitian ini bertujuan untuk mengetahui jenis korosi, kondisi pengendalian korosi yaitu coating yang diaplikasikan. Metodologi dalam penelitian ini adalah pengukuran pengurangan ketebalan struktur conveyor. Pada penelitian ini, pengamatan kondisi lingkungan meliputi temperatur udara rata-rata 280C, curah hujan rata-rata 233 mm dan kelembapan relatif 87%. Pengukuran tebal aktual struktur conveyor dilakukan dengan menggunakan alat Ultrasonic Thickness Gauge TT 130. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Metode pengendalian korosi yang diaplikasikan pada struktur conveyor yaitu metode coating. Coating yang digunakan adalah primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF dan top coating menggunakan Aliphatic Acrylic Modified Polyurethane.